2015
DOI: 10.1155/2015/307474
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Parkinson’s Disease Motor Symptom Asymmetry on Hand Performance: An Examination of the Grooved Pegboard Task

Abstract: This study examined the influence of motor symptom asymmetry in Parkinson's disease (PD) on Grooved Pegboard (GP) performance in right-handed participants. The Unified Parkinson's Disease Rating Scale was used to assess motor symptoms and separate participants with PD into two groups (right-arm affected, left-arm affected) for comparison with a group of healthy older adults. Participants completed the place and replace GP tasks two times with both hands. Laterality quotients were computed to quantify performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…All analyses except the asymmetry analysis incorporated the averaged parameter values. In order to determine body side asymmetries for bradykinesia and rigidity, the right minus left side difference between UPDRS items 22–26 were calculated when subjects were OFF medication [34].…”
Section: Methodsmentioning
confidence: 99%
“…All analyses except the asymmetry analysis incorporated the averaged parameter values. In order to determine body side asymmetries for bradykinesia and rigidity, the right minus left side difference between UPDRS items 22–26 were calculated when subjects were OFF medication [34].…”
Section: Methodsmentioning
confidence: 99%
“…tremor for the right and left side [20]. The side with the higher scores indicated more severe impairment, thus the side with the highest score was determined as the MAS.…”
Section: Plos Onementioning
confidence: 99%
“…2 Asymmetry helps distinguish PD from other motor disorders 3 and might influence factors like first symptom, disease survival, and time to diagnosis. 2,4 Despite neuroimaging evidence showing reduced dopamine uptake 5 and increased neurodegeneration 6 in the less affected side, the underlying pathophysiological mechanism remains unclear. 3 The literature conflicts on whether premorbid hand dominance influences PD symptom onset side, 4,[7][8][9] though handedness may affect motor performance and prognosis trajectories.…”
mentioning
confidence: 99%
“…4 Scharoun et al 4 found right-handed D-PD increased non-dominant hand usage, potentially switching hand preference as the disease progresses. Some research suggests D-PD has a more debilitating effect on hand performance than ND-PD, 10 while other studies report faster motor progression for ND-PD 4,5 or D-PD. 11,12 Quantifying asymmetrical motor impairment could help clinicians confirm PD diagnosis, refine prognosis, and design personalized rehabilitation plans.…”
mentioning
confidence: 99%
See 1 more Smart Citation